Pengaruh Good Corporate Governance Terhadap Profitabilitas - Siti Nuridah; Merliyana Merliyana; Elda Sagitarius; Selfa Novita Surachman (FEB Universitas Maritim Semarang, 2023)
The purpose of this research is to disclose influence of applicating good corporate governance to profitability in the company food and beverage listed on the Indonesia Stock Exchange in 2018-2021. This research is a type of descriptive research with a quantitative approach. The sampling technique was carried out using purposive sampling technique. So that the sample obtained was 14 food and beverage companies listed on the Indonesia Stock Exchange in 2018-2021 with a total observational data of 4 years of observation. The data collection technique used is the source of financial statement data using secondary data taken through the official website of the Indonesia Stock Exchange. The data analysis technique used in this study is multiple linear regression analysis with SPSS 25 software tools. The results of this study indicate that the audit committee has no significant effect on profitability. Independent commissioners have a significant effect on profitability. Institutional ownership has a significant effect on profitability. Then the audit committee, independent commissioners and institutional ownership have a simultaneous effect on profitability Keywords : audit committee, independent commissioners, Institutional ownership, profitability, ROA